Adaptasi akademik, sosial, personal, dan institusional : studi college adjustment terhadap mahasiswa tingkat pertama - Anisa Rahmadani; Yuliana Rahmawati Mukti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
Joining university for the first time is a challenging phase for first-year students. They are required to adapt not only to the academic context but to their personal, social, and emotional condition. The dynamics of college present a variety of challenges that arise as a result of the transition from high school to college. This study aims to analyze college adjustment of first-year students and the obstacles that arise from the academic, social, personal, and institutional dimensions. This study used mixed-method research. The sample was consisted of 235 first-year students of Al Azhar University (73.9% women) and filled out the Student Adaptation to College questionnaire. Qualitative data used purposive sampling to deepen the constraints felt by students in their first year. Semi structure interviews were conducted with 12 respondents to examine their experiences toward the first year of college. The results showed that 44.7% of first-year students had a low college adjustment level. Content analysis reveals that first-year students experienced varied academic, social, personal, and institutional problems. Therefore, the first-year student adapting process still needs attention from stakeholders.